Antifriction and wear-resistant medium-entropy alloy composite coating on hardware fitting surface and preparation method of antifriction and wear-resistant medium-entropy alloy composite coating
By preparing the FeCrNiAl0.5/MoS2 medium entropy alloy composite coating on the surface of the metal tool, the problem of wear and thinning of the metal tool in complex environments is solved, high wear resistance and low friction coefficient of the metal tool surface are achieved, and the operation safety and stability of the power system are improved.
Patent Information
- Application Number
- CN202411980047.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
When the metal tool is in service in a complex environment, it is prone to wear and thinning and damage at the stress points, resulting in unsafe and unstable power system operation.
A method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of the metal tool is adopted. By mixing Fe, Ni, Cr, Al powder and MoS2 powder for ball milling and drying, FeCrNiAl0.5/MoS2 composite powder is formed, and then a laser cladding process is used to form a medium-entropy alloy composite coating on the surface of the metal tool.
It effectively reduces the friction coefficient on the surface of the metal tool, significantly improves wear resistance, ensures the stability and safety of the metal tool for long-term service in complex environments, and improves the operational safety and stability of the power system.
Smart Images

Figure CN119776823A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of hardware used in overhead power transmission lines and a preparation method thereof. Background Art
[0002] Hardware is an important power equipment that connects, supports and protects various devices in the power system. Hardware needs to bear mechanical loads during service, and it is very easy to wear and thin at the connection points, thus becoming a weak link that causes line failures. In particular, the hardware used in overhead transmission lines is exposed to the natural environment and is affected by complex weather and environment such as wind, sand, lightning, dirt, ice and snow, which makes this type of hardware more susceptible to damage. In order to ensure the safe and stable operation of the power system, the maintenance of hardware has also become an important investment in the operation and maintenance of my country's transmission lines.
[0003] At present, the main methods to reduce the wear of hardware are to improve the stress distribution of the stress points by structural design and to improve the intrinsic mechanical properties of the hardware materials. Under complex meteorological conditions, external conditions may cause the structural stability of the hardware to change, thus causing unforeseen failures. Therefore, improving the intrinsic mechanical properties of the material is the safest and most reliable way. At present, most of the hardware used in my country are iron or aluminum parts with low surface hardness and poor wear resistance. Considering the two aspects of cost control and workpiece machinability, surface treatment technology can significantly improve the wear resistance of the material without changing the basic composition of the material. Chinese patent CN202011073698.1 discloses a method for preparing a nickel coating containing rare earth oxides and carbides on the surface of hardware by laser cladding. This method has the advantages of low production cost, high coating hardness and good wear resistance; Chinese patent CN202410018153.2 uses a laser cladding method to prepare a wear-resistant coating in which Fe, Ni, Cu and other elements form a γ-phase single-phase solid solution and a WC hard phase. The hard phase in the coating greatly improves the hardness of the coating, which plays a role in optimizing the wear resistance of the coating; Chinese patent CN201811285652.9 proposes a laser cladding method to prepare a wear-resistant and anti-corrosion coating containing silicon, carbon, tungsten, chromium, boron, aluminum and other elements. The coating improves the hardness of the coating through the hard phase, thereby having excellent wear resistance. Chinese patent CN202410889015.1 reports a treatment method for nitriding and then galvanizing the surface of steel fittings to form a high-hardness wear-resistant and corrosion-resistant composite coating; Chinese patent CN202410193208.3 proposes a method for preparing CrSiN / ZrN or CrW / CrN composite coatings by alternating deposition of arc ions and magnetron sputtering. This type of composite has the characteristics of high hardness, thus providing good wear-resistant protection for the hardware substrate. The above patents mainly improve the wear resistance of the protective layer on the surface of the hardware by increasing the hardness, and do not improve the wear resistance of the coating by reducing the friction coefficient. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of hardware and a preparation method, which can improve the wear resistance of the coating from the aspect of reducing the friction coefficient, and can effectively solve the problem that the stress points of the hardware are prone to wear and thinning and damage when serving in a complex environment, thereby improving the safety and stability of the operation of the power system.
[0005] In order to solve the above technical problems, the present invention provides, in a first aspect, a method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal surface, comprising the following steps:
[0006] Step S1, Fe powder, Ni powder, Cr powder and Al powder are mixed in a certain proportion and then added into an organic solvent for ball milling. After ball milling for 24 hours, a slurry containing mixed metal powders is obtained;
[0007] Step S2, adding a certain amount of MoS2 powder to the mixed metal powder, continuing ball milling for 24 hours and then drying at 90°C for 10 hours, and sieving to obtain a composite powder;
[0008] Step S3, pretreatment of the surface of the hardware material: removing the rust layer and stains on the surface of the hardware material by sanding, then rinsing with clean water and drying with cold air;
[0009] Step S4: using a laser cladding process to coat the composite powder obtained after the sieving process in step S2 on the surface of the hardware to form a medium entropy alloy composite coating.
[0010] A further improvement of the technical solution of the present invention is that the mixed metal powder in step S1 is FeCrNiAl 0.5 , wherein the molar ratio of Fe powder, Ni powder, Cr powder and Al powder is 1:1:1:0.5.
[0011] A further improvement of the technical solution of the present invention is that the particle sizes of the Fe powder, Ni powder, Cr powder and Al powder in step S1 are all -600 mesh to +1000 mesh.
[0012] A further improvement of the technical solution of the present invention is that the solvent used for ball milling in step S1 is polyvinyl alcohol or alcohol.
[0013] A further improvement of the technical solution of the present invention is that the amount of MoS2 powder added in step S2 is the mixed metal powder FeCrNiAl 0.5 0.5~2wt.%, MoS2 powder has a particle size of less than 200nm.
[0014] A further improvement of the technical solution of the present invention is that the composite powder sieved in step S2 is FeCrNiAl 0.5 / MoS2, composite powder FeCrNiAl 0.5 / The particle size of MoS2 is -600 mesh to +1000 mesh.
[0015] A further improvement of the technical solution of the present invention is that the laser cladding process parameters in step S4 include laser cladding speed controlled at 80-300 mm / s, spot diameter of 3 mm, laser power of 6 kW, powder feeding amount of 10-20 g / min, overlap rate of 50%, and inert gas protection during the laser cladding process.
[0016] A further improvement of the technical solution of the present invention is that the inert gas used in step S4 is nitrogen or argon.
[0017] A further improvement of the technical solution of the present invention is that the thickness of the medium-entropy alloy composite coating in step S4 is greater than 80 μm.
[0018] In a second aspect, the present invention provides a friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of a hardware, which is prepared by the above-mentioned preparation method.
[0019] Due to the adoption of the above technical solution, the technical progress achieved by the present invention is:
[0020] 1. The friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of a hardware and its preparation method of the present invention improve the wear resistance of the coating from the aspect of reducing the friction coefficient, can effectively solve the problem that the hardware is prone to wear and thinning and damage at the stress point when serving in a complex environment, and improve the safety and stability of the power system operation;
[0021] 2. The method for preparing the friction-reducing and wear-resistant medium entropy alloy composite coating on the surface of the hardware of the present invention is to prepare a mixed powder with uniform composition by high-speed ball milling, and to obtain FeCrNiAl on the surface of the hardware material by laser cladding. 0.5 / MoS2 medium entropy alloy composite coating, the coating is well bonded to the substrate, the surface is smooth and dense; the method has the advantages of simple preparation process, fast coating preparation speed, controllable coating thickness, etc., and can be widely promoted and applied;
[0022] 3. The method for preparing the friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of the hardware of the present invention proposes to use a laser cladding method to prepare a high-hardness medium-entropy alloy coating on the surface of the hardware, and at the same time add a lubricating phase to reduce the friction coefficient of the coating to obtain a friction-reducing and wear-resistant medium-entropy alloy composite coating with good protective performance; the friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of the hardware has an extremely low friction coefficient and excellent wear resistance. The matrix material FeCrNiAl in the composite coating is 0.5 The medium entropy alloy has extremely high hardness and coating toughness; the MoS2 in the composite coating has a lubricating effect and can greatly reduce the friction coefficient of the coating. Therefore, the FeCrNiAl0.5 / MoS2 medium entropy alloy composite coating of the present invention has the characteristics of high hardness and low friction coefficient, and its wear resistance is excellent, which provides good surface protection for the hardware substrate, and can effectively solve the problem that the hardware is prone to wear and thinning and damage at the stress point when serving in a complex environment, thereby improving the safety and stability of the power system operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The FeCrNiAl in Examples 1 to 3 of the present invention 0.5 XRD pattern of / MoS2 medium entropy alloy composite coating;
[0024] Figure 2 The FeCrNiAl in Examples 1 to 3 of the present invention0.5 SEM photo of the interface between the / MoS2 medium entropy alloy composite coating and the substrate;
[0025] Figure 3 The FeCrNiAl in Examples 1 to 3 of the present invention 0.5 Scanning electron microscope photograph of / MoS2 medium entropy alloy composite coating after friction and wear test. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with embodiments:
[0027] The present invention provides a method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a hardware surface, comprising the following steps:
[0028] Step S1: Fe powder, Ni powder, Cr powder and Al powder are mixed in a certain proportion and then added into an organic solvent for ball milling. The solvent used for ball milling is polyvinyl alcohol or alcohol. After ball milling for 24 hours, a slurry containing mixed metal powders is obtained. The mixed metal powders are FeCrNiAl 0.5 The molar ratio of Fe powder, Ni powder, Cr powder and Al powder is 1:1:1:0.5. The particle sizes of Fe powder, Ni powder, Cr powder and Al powder are all -600 mesh to +1000 mesh, preferably +800 mesh.
[0029] Step S2: adding a certain amount of MoS2 powder to the mixed metal powder FeCrNiAl 0.5 Specifically, the amount of MoS2 powder added is the mixed metal powder FeCrNiAl 0.5 After 24 hours of ball milling, the powder was dried at 90°C for 10 hours and sieved to obtain composite powder FeCrNiAl suitable for laser cladding. 0.5 / MoS2, composite powder FeCrNiAl 0.5 / The particle size of MoS2 is -600 mesh to +1000 mesh, preferably +800 mesh.
[0030] Step S3, pretreatment of the surface of the hardware material: removing the rust layer and stains on the surface of the hardware material by sanding, then rinsing with clean water and drying with cold air;
[0031] Step S4, using a laser cladding process to coat the composite powder obtained after the sieving process in step S2 on the surface of the hardware to form a medium entropy alloy composite coating, the laser cladding process parameters include laser cladding speed controlled at 80-300 mm / s, spot diameter of 3 mm, laser power of 6 kW, powder feeding amount of 10-20 g / min, overlap rate of 50%, and inert gas nitrogen or argon is used for protection during the laser cladding process. The thickness of the medium entropy alloy composite coating should be greater than 80 μm.
[0032] The present invention also provides a friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of a hardware, which is prepared by the above-mentioned preparation method. The hardness of the medium-entropy alloy composite coating is not less than 1000 HV, the friction coefficient is less than 0.4, and the wear resistance is excellent.
[0033] Example 1
[0034] First, prepare the composite powder: take Fe powder, Ni powder, Cr powder and Al powder with a particle size of -600 mesh to +1000 mesh, mix them evenly in a molar ratio of 1:1:1:0.5, then add them into an alcohol solvent for ball milling, and obtain a slurry containing mixed metal powder after ball milling for 24 hours; then add MoS2 powder with a mass of 0.5wt.% of the mixed metal powder into the slurry, continue ball milling for 24 hours, and then dry at 90°C for 10 hours, and obtain a composite powder of -600 mesh to +1000 mesh after sieving.
[0035] Subsequently, FeCrNiAl was prepared by laser cladding process on the surface of Q235 steel, a metal material, after sandpaper polishing. 0.5 / MoS2 medium entropy alloy composite coating, cladding speed is 80mm / s, spot diameter is 3mm, laser power is 6kW, powder feeding amount is 10g / min, overlap rate is controlled at about 50%, inert gas is used for protection during laser cladding treatment, and uniform and dense FeCrNiAl 0.5 / MoS2 medium entropy alloy composite coating.
[0036] See also Figure 1 The obtained FeCrNiAl 0.5 The matrix phase of the MoS2 medium entropy alloy composite coating is a body-centered cubic structure.
[0037] See also Figure 2 The obtained FeCrNiAl 0.5 The / MoS2 medium entropy alloy composite coating is well bonded to the substrate, the coating is uniform and dense, without obvious defects, and meets the requirements of wear-resistant coating.
[0038] The hardness of the obtained coating was tested using a HVS-1000Z microhardness tester. The test parameters were: loading load of 0.2 kg, holding time of 10 s, and the average value of 5 test points. The microhardness value of the obtained coating was 1160.4±8.3 HV, which was much higher than the hardness value of the substrate material.
[0039] The friction and wear life of the prepared coating was averaged using a QZ-301II multifunctional friction tester. The specific parameters are: the prepared coating sample and the Φ=6mm Si3N4 ceramic ball friction pair were used for reciprocating sliding, the sliding frequency was 5Hz, the load was 5N, the ambient temperature was (25±2)℃, and the wear time was set to 30min. The relationship between the friction coefficient and the sliding time is shown in Figure 1 As shown in the curve, the average friction coefficient is 0.275, which is much smaller than the friction coefficient of the base material; as shown in Table 1, the wear loss of the sample is 0.47 mg, indicating that the prepared FeCrNiAl 0.5 The MoS2 medium entropy alloy composite coating has an extremely low friction coefficient and good wear resistance, and can provide good protection for hardware.
[0040] Example 2
[0041] First, prepare the composite powder: take Fe powder, Ni powder, Cr powder and Al powder with a particle size of -600 mesh to +1000 mesh, mix them evenly in a molar ratio of 1:1:1:0.5, then add them into an alcohol solvent for ball milling, and obtain a slurry containing mixed metal powder after 24 hours of ball milling; then add MoS2 powder with a particle size of 2000 mesh and a mass of 1.2 wt.% of the mixed metal powder into the slurry, continue ball milling for 24 hours, and then dry at 90°C for 10 hours, and obtain a composite powder of -600 mesh to +1000 mesh after sieving.
[0042] Subsequently, FeCrNiAl was prepared by laser cladding process on the surface of Q235 steel, a metal material, after sandpaper polishing. 0.5 / MoS2 medium entropy alloy composite coating, cladding speed is 150mm / s, spot diameter is 3mm, laser power is 6kW, powder feeding amount is 15g / min, overlap rate is controlled at about 50%, inert gas is used for protection during laser cladding treatment, and uniform and dense FeCrNiAl 0.5 / MoS2 medium entropy alloy composite coating.
[0043] See also Figure 1 The obtained FeCrNiAl 0.5 The matrix phase of the MoS2 medium entropy alloy composite coating is a body-centered cubic structure.
[0044] See also Figure 2 The obtained FeCrNiAl 0.5 The / MoS2 medium entropy alloy composite coating also bonds very well with the substrate. The coating is uniform and dense without obvious defects, meeting the requirements of wear-resistant coating.
[0045] The hardness of the obtained coating was tested using a HVS-1000Z microhardness tester. The test parameters were: loading load of 0.2 kg, holding time of 10 s, and the average value of 5 test points. The microhardness value of the obtained coating was 1124.3±12.5 HV, which was much higher than the hardness value of the substrate material.
[0046] The friction and wear life of the prepared coating was averaged using a QZ-301II multifunctional friction tester. The specific parameters are: the prepared coating sample and the Φ=6mm Si3N4 ceramic ball friction pair were used for reciprocating sliding, the sliding frequency was 5Hz, the load was 5N, the ambient temperature was (25±2)℃, and the wear time was set to 30min. The relationship between the friction coefficient and the sliding time is shown in Figure 1 As shown in the curve, the average friction coefficient is 0.208, which is much smaller than the friction coefficient of the base material; as shown in Table 1, the wear loss of the sample is 0.38 mg, which is lower than the wear loss of the base material, indicating that the prepared FeCrNiAl 0.5 The MoS2 medium entropy alloy composite coating has an extremely low friction coefficient and good wear resistance, and can provide good protection for hardware.
[0047] Example 3
[0048] First, prepare the composite powder: take Fe powder, Ni powder, Cr powder and Al powder with a particle size of -600 mesh to +1000 mesh, mix them evenly in a molar ratio of 1:1:1:0.5, then add them into an alcohol solvent for ball milling, and obtain a slurry containing mixed metal powder after 24 hours of ball milling; then add MoS2 powder with a particle size of 2000 mesh and a mass of 2.0wt.% of the mixed metal powder into the slurry, continue ball milling for 24 hours, and then dry at 90°C for 10 hours, and obtain a composite powder of -600 mesh to +1000 mesh after sieving.
[0049] Subsequently, FeCrNiAl was prepared by laser cladding process on the surface of Q235 steel, a metal material, after sandpaper polishing. 0.5 / MoS2 medium entropy alloy composite coating, cladding speed is 300mm / s, spot diameter is 3mm, laser power is 6kW, powder feeding amount is 30g / min, overlap rate is controlled at about 50%, inert gas is used for protection during laser cladding treatment, and uniform and dense FeCrNiAl 0.5 / MoS2 medium entropy alloy composite coating.
[0050] See also Figure 1 The obtained FeCrNiAl 0.5 The matrix phase of the MoS2 medium entropy alloy composite coating is a body-centered cubic structure.
[0051] See also Figure 2The obtained FeCrNiAl 0.5 The / MoS2 medium entropy alloy composite coating also bonds very well with the substrate. The coating is uniform and dense without obvious defects, meeting the requirements of wear-resistant coating.
[0052] The hardness of the obtained coating was tested using a HVS-1000Z microhardness tester. The test parameters were: loading load of 0.2 kg, holding time of 10 s, and the average value of 5 test points. The microhardness value of the obtained coating was 1124.3±12.5 HV, which was much higher than the hardness value of the substrate material.
[0053] The friction and wear life of the prepared coating was averaged using a QZ-301II multifunctional friction tester. The specific parameters are: the prepared coating sample and the Φ=6mm Si3N4 ceramic ball friction pair were used for reciprocating sliding, the sliding frequency was 5Hz, the load was 5N, the ambient temperature was (25±2)℃, and the wear time was set to 30min. The relationship between the friction coefficient and the sliding time is shown in Figure 1 As shown in the curve, the average friction coefficient is 0.201, which is much smaller than the friction coefficient of the base material; as shown in Table 1, the wear loss of the sample is 0.49 mg, indicating that the prepared FeCrNiAl 0.5 The MoS2 medium entropy alloy composite coating has an extremely low friction coefficient and good wear resistance, and can provide good protection for hardware.
[0054] Comparative Example 1
[0055] Compared with Example 1, the addition amount of MoS2 powder in this comparative example is 0.4wt.%, and the prepared FeCrNiAl 0.5 The reduction of lubricating phase in the MoS2 / MoS2 medium entropy alloy composite coating caused its average friction coefficient to increase to 0.398 and the wear loss to increase to 0.81 mg. Therefore, insufficient addition of MoS2 lubricating phase in the composite powder will increase the friction coefficient of the coating and affect the wear resistance of the coating.
[0056] Comparative Example 2
[0057] Compared with Example 1, the cladding speed in this comparative example is 70 mm / s, the prepared coating is not well bonded to the substrate, the microhardness decreases, the friction coefficient increases, and the wear amount increases significantly. Therefore, too low a scanning speed will cause uneven temperature distribution in the molten pool, and greater thermal stress will be generated during solidification and cooling. 0.5 Cracks and other defects appear at the interface between the MoS2 medium-entropy alloy composite coating and the substrate, affecting the wear resistance of the coating.
[0058] Comparative Example 3
[0059] Compared with Example 1, the powder feeding rate in this comparative example is 9 g / min, and the prepared FeCrNiAl 0.5 The / MoS2 medium entropy alloy composite coating is not well bonded to the substrate, the microhardness decreases, the friction coefficient increases, and the wear volume increases significantly. Therefore, when the powder feeding amount is insufficient, the laser energy received by the powder increases, the heat in the molten pool increases, and greater thermal stress is generated during solidification and cooling. 0.5 Cracks and other defects appear at the interface between the MoS2 medium-entropy alloy composite coating and the substrate, affecting the wear resistance of the coating.
[0060] Comparative Example 4
[0061] Compared with Example 3, the addition amount of MoS2 powder in this comparative example is 3.0wt.%, and the prepared FeCrNiAl 0.5 The MoS2 lubricating phase in the MoS2 medium entropy alloy composite coating agglomerates, resulting in a decrease in hardness and an increase in wear. Therefore, excessive addition of MoS2 lubricating phase in the composite powder will lead to agglomeration of the second phase, reduce the uniformity of the coating, and affect the wear resistance of the coating.
[0062] Comparative Example 5
[0063] Compared with Example 3, the cladding speed in this comparative example is 310 mm / s, and the prepared FeCrNiAl 0.5 The hardness of the MoS2 / MoS2 medium entropy alloy composite coating decreases, the friction coefficient increases, and the wear volume increases. Therefore, the cladding speed is too high, the laser energy absorbed by the powder is insufficient, the melting speed is slow, and the molten pool width is narrow and the existence time is short. The impurities in the molten pool cannot float up in time and remain in the cladding layer as inclusions. These defects eventually lead to a decrease in hardness and affect the wear resistance of the coating.
[0064] Comparative Example 6
[0065] Compared with Example 3, the powder feeding rate in this comparative example is 30g / min, and the prepared FeCrNiAl 0.5 / MoS2 medium entropy alloy composite coating hardness decreases, friction coefficient increases, and wear increases. Therefore, when the powder feeding amount is too large, the thickness of the cladding layer increases, the internal stress release during the cladding process is difficult, and it is easy to cause defects such as cracks; at the same time, the thickness of the cladding layer increases and the depth of the molten pool deepens, and impurities cannot float up in time before the molten pool solidifies, and are retained in the molten pool to form inclusions. These defects will eventually reduce the microhardness of the cladding layer, increase the friction coefficient, and affect the wear resistance of the coating.
[0066] In order to further demonstrate the technical effect of the present invention, the present invention conducted relevant tests on hardness, friction coefficient and wear amount on Examples 1-3 and Comparative Examples 1-6, and the obtained test results are shown in Table 1.
[0067] Table 1 Hardness and wear resistance of coating
[0068] sample <![CDATA[Hardness (HV 0.2 )]]> Friction coefficient Wear amount (mg) Q235 steel substrate 183.1±11.8 0.613 2.09 Example 1 1160.4±8.3 0.275 0.47 Example 2 1124.3±12.5 0.208 0.38 Example 3 1032.8±25.2 0.201 0.49 Comparative Example 1 1180.7±5.6 0.398 0.81 Comparative Example 2 981.3±30.1 0.341 0.92 Comparative Example 3 1058.8±34.4 0.352 0.86 Comparative Example 4 924.6±29.8 0.264 0.82 Comparative Example 5 905.6±32.3 0.326 0.98 Comparative Example 6 974.2±29.6 0.342 0.93
[0069] In summary, the FeCrNiAl 0.5 / MoS2 medium entropy alloy composite coating, the preparation method is to mix Fe powder, Ni powder, Cr powder and Al powder and then ball mill to form a slurry, then add lubricating phase MoS2 and continue to ball mill, dry and sieve to obtain a mixed powder suitable for laser cladding treatment. Then, through the laser cladding rapid process after parameter optimization, a uniform and dense FeCrNiAl layer with good bonding with the substrate is prepared on the surface of the metal material. 0.5 / MoS2 medium entropy alloy composite coating. The matrix material of the composite coating is FeCrNiAl 0.5 Medium entropy alloys have extremely high hardness and coating toughness; MoS2 in the composite coating has a lubricating effect and can greatly reduce the friction coefficient of the coating. 0.5 The / MoS2 medium entropy alloy composite coating has the characteristics of high hardness and low friction coefficient, and its wear resistance is excellent, which can provide good surface protection for the hardware substrate.
[0070] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.
[0071] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.
Claims
1. A method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface, characterized in that: The steps include: Step S1, Fe powder, Ni powder, Cr powder and Al powder are mixed in a certain proportion and then added into an organic solvent for ball milling. After ball milling for 24 hours, a slurry containing mixed metal powders is obtained; Step S2, adding a certain amount of MoS2 powder to the mixed metal powder, continuing ball milling for 24 hours and then drying at 90°C for 10 hours, and sieving to obtain a composite powder; Step S3, pretreatment of the surface of the hardware material: removing the rust layer and stains on the surface of the hardware material by sanding, then rinsing with clean water and drying with cold air; Step S4: using a laser cladding process to coat the composite powder obtained after the sieving process in step S2 on the surface of the hardware to form a medium entropy alloy composite coating.
2. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 1, characterized in that: The mixed metal powder in step S1 is FeCrNiAl 0.5 , wherein the molar ratio of Fe powder, Ni powder, Cr powder and Al powder is 1:1:1:0.
5.
3. The method for preparing a friction-reducing and wear-resistant entropy alloy composite coating on a metal fitting surface according to claim 1, characterized in that: The particle sizes of the Fe powder, Ni powder, Cr powder and Al powder in step S1 are all -600 mesh to +1000 mesh.
4. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 1, characterized in that: The solvent used for ball milling in step S1 is polyvinyl alcohol or alcohol.
5. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 2, characterized in that: The amount of MoS2 powder added in step S2 is the mixed metal powder FeCrNiAl 0.5 0.5~2wt.%, MoS2 powder has a particle size of less than 200nm.
6. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 5, characterized in that: The composite powder after sieving in step S2 is FeCrNiAl 0.5 / MoS2, composite powder FeCrNiAl 0.5 / The particle size of MoS2 is -600 mesh to +1000 mesh.
7. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 1, characterized in that: The laser cladding process parameters in step S4 include laser cladding speed controlled at 80-300 mm / s, spot diameter of 3 mm, laser power of 6 kW, powder feeding amount of 10-20 g / min, overlap rate of 50%, and inert gas protection during the laser cladding process.
8. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 7, characterized in that: The inert gas used in step S4 is nitrogen or argon.
9. The method for preparing a friction-reducing and wear-resistant medium-entropy alloy composite coating on a metal fitting surface according to claim 8, characterized in that: The thickness of the medium entropy alloy composite coating in step S4 is greater than 80 μm.
10. A friction-reducing and wear-resistant medium-entropy alloy composite coating on the surface of a metal fitting, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Laser cladding surface reinforcing method for electric power connection fitting
CN109536942A
Laser cladding coating for electric power fittings and cladding method thereof
CN114351132A
Wear-resistant and corrosion-resistant coating on surface of electric power connection fitting and preparation method of wear-resistant and corrosion-resistant coating
CN117821966A
Coating method and device for surface protection of electric power fittings
CN117987774A
Wear-resistant and corrosion-resistant composite coating as well as preparation method and application thereof
CN118792604A